Bone Cement Cranioplasty Reduces Cerebrospinal Fluid Leak Rate after Microvascular Decompression: A Single-Institutional Experience - Wolfson, Daniel I.; Magarik, Jordan A.; Godil, Saniya S.; Shah, Hamid M.; Neimat, Joseph S.; Konrad, Peter E.; Englot, Dario J. (Journal of Neurological Surgery Part B: Skull Base, 2020)
Background Microvascular decompression (MVD) is a common surgical treatment for cranial nerve compression, though cerebrospinal fluid (CSF) leak is a known complication of this procedure. Bone cement cranioplasty may reduce rates of CSF leak.Objective To compare rates of CSF leak before and after implementation of bone cement cranioplasty for the reconstruction of cranial defects after MVD.Methods Retrospective chart review was performed of patients who underwent MVD through retrosigmoid craniectomy for cranial nerve compression at a single institution from 1998 to 2017. Study variables included patient demographics, medical history, type of closure, and postoperative complications such as CSF leak, meningitis, lumbar drain placement, and ventriculoperitoneal shunt insertion. Cement and noncement closure groups were compared, and predictors of CSF leak were assessed using a multivariate logistic regression model.Results A total of 547 patients treated by 10 neurosurgeons were followed up for more than 20 years, of whom 288 (52.7%) received cement cranioplasty and 259 (47.3%) did not. Baseline comorbidities were not significantly different between groups. CSF leak rate was significantly lower in the cement group than in the noncement group (4.5 vs. 14.3%; p < 0.001). This was associated with significantly fewer patients developing postoperative meningitis (0.7 vs. 5.2%; p = 0.003). Multiple logistic regression model demonstrated noncement closure as the only independent predictor of CSF leak (odds ratio: 3.55; 95% CI: 1.78–7.06; p < 0.001).Conclusion CSF leak is a well-known complication after MVD. Bone cement cranioplasty significantly reduces the incidence of postoperative CSF leak and other complications. Modifiable risk factors such as body mass index were not associated with the development of CSF leak.
Keywords: bone cement; cranioplasty; CSF leak; methyl methacrylate; microvascular decompression